The Persian Version of the "Participation Measure-3 Domains, 4 Dimensions": Translation, Cultural Adaptation, Face and Content Validity - Diba Sharifi; Laleh Lajevardi; Ghorban Taghizadeh; Akram Azad (Function and Disability Journal)
Background and Objectives: Investigating the impact of occupational therapy interventions on the participation levels of adults with stroke is crucial due to its significant influence on their satisfaction and quality of life (QOL). Therefore, it is essential to provide a more comprehensive understanding and an accurate assessment of individual participation, while ensuring the affordability of evaluation tools. This study aims to translate and evaluate the face and content validity of the Persian version of the participation measure–3 domains, 4 dimensions (PM-3D4D) questionnaire in adults with chronic stroke. Methods: This methodological study was conducted following the international QOL assessment (IQOLA) protocol after obtaining permission from the test developer. The Persian version of PM-3D4D was created, and the face and content validity were evaluated with the participation of 20 adult patients with chronic stroke and 15 occupational and physiotherapists experienced in stroke rehabilitation. Both quantitative and qualitative approaches were utilized to assess face validity, while the content validity index (CVI) (to evaluate clarity, relevance, simplicity, and of items) and content validity ratio (CVR) (to establish the necessity of items) were applied to evaluate content validity. Results: Participants’ opinions regarding all items of the questionnaire were favorable; thus, the Persian version was entirely clear, appropriate, and satisfactory in terms of both structure and content. In terms of importance, quantitative assessments of face validity showed that all items had impact scores above 1.5 and were thus accepted. The CVR and CVI results confirmed that all items were necessary, simple, sufficiently clear, and relevant to the concept of participation. Conclusion: The Persian version of the PM-3D4D questionnaire demonstrates good face and content validity and warrants further investigation in psychometrics as a tool to measure participation among adults with chronic stroke.